1987
DOI: 10.1002/ijc.2910390310
|View full text |Cite
|
Sign up to set email alerts
|

Sister chromatid exchange induction by benzo(a)pryene in cultured peripheral blood lymphocytes of lung cancer patients and healthy individuals with or without familial history of neoplasms

Abstract: The inducibility of sister chromatid exchanges (SCEs) by benzo(a)pyrene (BP) was studied in cultured peripheral blood lymphocytes of 15 untreated lung cancer patients and 25 healthy persons including 11 high- and 14 low-cancer-risk individuals tentatively classified by the familial history of lung cancer and other neoplasms. The baseline SCE frequency in cultured lymphocytes was significantly high in lung cancer patients, as compared with all healthy persons or low-cancer-risk individuals. Following exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…These include reports on malignant lymphoma (Kurvink et al, 1978), cancer of the breast (Livingston et al, 1983), thyroid (Krizman et al, 1987), and lung (Hopkin and Evans, 1980;Dusaka et al, 1987), acute lymphocytic leukaemia (Otter et al, 1979) and cancer of uterine cervix (Mitra et al, 1982). However, contrary findings have also been reported (Husum et al, 1981;Crossen et al, 1981;Hollander et al, 1978;Cheng et al, 1979).…”
mentioning
confidence: 81%
“…These include reports on malignant lymphoma (Kurvink et al, 1978), cancer of the breast (Livingston et al, 1983), thyroid (Krizman et al, 1987), and lung (Hopkin and Evans, 1980;Dusaka et al, 1987), acute lymphocytic leukaemia (Otter et al, 1979) and cancer of uterine cervix (Mitra et al, 1982). However, contrary findings have also been reported (Husum et al, 1981;Crossen et al, 1981;Hollander et al, 1978;Cheng et al, 1979).…”
mentioning
confidence: 81%
“…Induced SCEs have been correlated positively with somatic gene mutations [15], chromosomal aberrations [16], and neoplastic transformation [17]. SCE assay has been used successfully to monitor human exposure to occupational and environmental mutagens [HI, and applications for monitoring the effectiveness of cancer chemotherapic agents [19,20] and screening for individuals with high cancer risk [21] have been suggested. Several studies of neoplasia reported increased levels of spontaneous SCEs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of neoplasia reported increased levels of spontaneous SCEs. High SCE rates were observed in lymphocytes from patients with breast cancer [22], cervical cancer [23], lung cancer [21], leukemia [24], and metastatic variants of murine B16 melanoma and human astrocytomas [25]. SCE has occurred with increased frequency in lymphoma cell lines and has been correlated positively with extent of karyotypic abnormalities [26].…”
Section: Introductionmentioning
confidence: 99%
“…An indication of such a possibility was obtained in a study by Hopkin and Evans [3], who showed that the SCE-response to cigarette smoke condensate in lymphocytes from lung cancer patients was more marked than in cells of those with similar smoking habits but who were without cancer. Following exposure to benzo(a)pyrene in vitro, lymphocytes of lung cancer patients and high-cancerrisk individuals exhibited significantly greater SCE yields than those of persons at low risk [4]. In addition, increased levels of lymphocyte SCEs were observed among breast cancer patients before treatment [5,6].…”
Section: Introductionmentioning
confidence: 99%